Comparative evaluation of the healing potential of excision wound using Nano- formulations of silver, gold, or their mixture: In-silico and in vivo approaches - Abeer A. Mabrouk; Sameh H. Ismail; Ahmed G. Soliman; Mervat M. Omran (PLoS ONE, 2026)
The medical use of metal nanoparticles is recommended to reduce adverse effects and improve curative action when compared to their pure ions. Current research discussed the healing effect of topical formulations of silver, gold, and their mixtures of nanoparticles on excision wounds in rat models. The physicochemical factors of the prepared nanoparticles were measured by dynamic light scattering (DLS), Zeta potential, atomic force microscopy (AFM), and transmission electron microscopy (TEM). Thirty-two albino rats were divided into six groups: wound untreated, silver nanoparticles (AgNps) treated, gold nanoparticles (AuNps), silver-gold nanoparticles (Ag/AuNps 1:1) mixture treated, and fusidic acid (reference drug) treated groups, respectively. Management was performed daily for 21 days. In all groups, the percentages of contraction area and histological investigation of the wound area were investigated. Myeloperoxidase (MPO), nitric oxide (NO), vascular endothelial growth factor (VEGF), hydroxyproline, hexosamine, and collagen deposition using Masson’s trichrome stain (MT) as a biomarker of wound healing activity were measured. An in-silico study investigated the molecular interaction of the metal nanoformulations with various protease enzymes involved in inflammation and the absorption, distribution, metabolism, excretion, and toxicity (ADMET) properties of the examined metals. The AgNPs and AuNPs have efficient wound-repairing activity, as evident from the wound shrinkage and enhanced wound healing. Metal nanoformulations have effective wound healing activity by enhancing angiogenesis and collagen formation.